2020
DOI: 10.1007/s40520-020-01475-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel behavioural INTErvention to REduce Sitting Time in older adults undergoing orthopaedic surgery (INTEREST): results of a randomised-controlled feasibility study

Abstract: Background Osteoarthritis is a prevalent condition in older adults that causes many patients to require a hip or knee replacement. Reducing patients' sedentariness prior to surgery may improve physical function and post-operative outcomes. Methods We conducted a pragmatic randomised-controlled feasibility study with 2:1 allocation into intervention or usual care groups. The intervention, based on Self-Determination Theory, involved techniques to reduce sedentary behaviour, including motivational interviewing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…This is consistent with other research in post-menopausal women, whereby a greater number of breaks in SB resulted in a 10% reduction in the odds of being diagnosed with osteoporosis/osteopenia [35]. A small study in frailer older adults found that breaking SB on a roughly hourly basis throughout the day improved physical function (timed up and go and 30 second chair stand) over a 10-week period, with no significant change in total ST or PA [36]. Similarly, Aunger et al [37] reported clinically significant improvement in physical function with non-significant increases in daily steps and time spent upright, despite non-significant decreases in SB.…”
Section: Summary Of Evidencesupporting
confidence: 89%
“…This is consistent with other research in post-menopausal women, whereby a greater number of breaks in SB resulted in a 10% reduction in the odds of being diagnosed with osteoporosis/osteopenia [35]. A small study in frailer older adults found that breaking SB on a roughly hourly basis throughout the day improved physical function (timed up and go and 30 second chair stand) over a 10-week period, with no significant change in total ST or PA [36]. Similarly, Aunger et al [37] reported clinically significant improvement in physical function with non-significant increases in daily steps and time spent upright, despite non-significant decreases in SB.…”
Section: Summary Of Evidencesupporting
confidence: 89%
“…The only area of overlap was that both studies reported participants' views of personal tailoring. Patients in the study by Aunger et al [72] felt their sedentary behavior reduction goals were well suited to their individual circumstances, but most patients still had difficulties attaining their goals. Health professionals in the study by Snowden et al [86] highlighted that tailoring the alcohol consumption reduction intervention and associated screening to patients' individual needs helped keep their interactions positive.…”
Section: Views Studiesmentioning
confidence: 96%
“…The remaining two studies were mixed methods pilot and/or feasibility studies that investigated interventions aimed at reducing sedentary behavior [72] or alcohol consumption [86]. The only area of overlap was that both studies reported participants' views of personal tailoring.…”
Section: Views Studiesmentioning
confidence: 99%
“…This means that researchers targeting non‐Western populations may have to develop and validate new domain‐specific questionnaires against objective devices or direct observation prior to beginning their study to ensure that key, relevant behaviors are included. Even within industrialized contexts, many questionnaires such as the Measure of Older Adults Sedentary Time (Gardiner et al, 2011 ) focus on “leisure time” activities but miss key behaviors such as eating, which is typically seated and occupies a large amount of the day (Aunger et al, 2020 ). It is also important to note that questionnaires have generally been written and validated in English and may require specific validation for use in other languages.…”
Section: Subjective Measurement Of Sedentary Behaviormentioning
confidence: 99%
“…They can also be delivered in the native languages of the population of interest. PDR approaches are also able to capture sedentary behaviors that are common but often excluded from questionnaires, such as sitting to eat a meal (Aunger et al, 2020 ). The semi‐structured interview nature of PDR also lends itself to clarifications to understand the postures associated with each activity the participant reports.…”
Section: Subjective Measurement Of Sedentary Behaviormentioning
confidence: 99%